Influence of employment on poverty reduction in Costa Rica. A quantitative analysis. - Otoya Chavarría, Marco (2025)
This article analyzes the influence of employment on poverty reduction, considering its relationship with other socio-demographic factors. For this purpose, a novel econometric approach is used the use qualitative information by means of the coding technique based on representative values, using data available in the National Household Survey (ENAHO). This approach replaces the use of "k-1" (dichotomous variables, commonly used in econometric studies), since it proposes the construction of numerical variables based on categorical variables from the ENAHO, in such a way that dimensions such as the level of job quality, job hierarchy, household vulnerability, among others, are adequately represented. The results indicate that, based on the average values of the explanatory variables for the population living in poverty, the estimated probability of remaining in poverty is 65.60%. However, if this same group were to attain at least a complete secondary education, an intermediate command of information and communication technologies (ICT) and English, at least half of the quality working conditions, and a position as an operator or higher, the probability of being in poverty would be reduced by 55 percentage points to 9.01%. In other words, if the conditions of people living in poverty were improved and the possibilities of accessing relatively formal employment were created, it is estimated that the majority of these households could be lifted out of poverty. These findings highlight the impact of quality employment and education on poverty reduction and are fundamental for the design of effective public policies that promote the reactivation of the local labor market, technical and professional training, social mobility, and labor inclusion.